The association between community-level economic deprivation and incidences of emergency department visits on account of attempted suicides in Maryland - Akinyemi, Oluwasegun; Ogundare, Temitope; Weldeslase, Terhas; Andine, Tsion; Fasokun, Mojisola; Odusanya, Eunice; Hughes, Kakra; Mallory, Williams; Luo, Guoyang; Cornwell, Edward (Frontiers in Public Health, 2024)
Background Suicide is a major cause of mortality in the United States, accounting for 14.5 deaths per 100,000 population. Many emergency department (ED) visits in the United States are due to attempted suicides. Suicide attempts predict subsequent completed suicides. Socioeconomic factors, such as community-level socioeconomic deprivation, significantly affect many traditional risk factors for attempted suicides and suicides. Aim To determine the association between community-level socioeconomic deprivation and ED visits for attempted suicide in Maryland. Methods A retrospective analysis of attempted suicides in the Maryland State Emergency Department Database from January 2018 to December 2020. Community-level socioeconomic deprivation was measured using the Distress Community Index (DCI). Multivariate regression analyses were conducted to identify the association between DCI and attempted suicides/self-harm. Results There were 3,564,987 ED visits reported in the study period, with DCI data available for 3,236,568 ED visits; 86.8% were younger than 45 years, 64.8% were females, and 54.6% non-Hispanic Whites. Over the study period, the proportion of ED visits due to attempted suicide was 0.3%. In the multivariate logistic regression, compared to prosperous zones, those in comfortable (OR = 0.80, 95% CI: 0.73–0.88, p < 0.01), Mid-Tier (OR = 0.76, 95%CI:0.67–0.86, p < 0.01), At-Risk (OR = 0.77; 95%CI: 0.65–0.92, p < 0.01) and Distressed zones (OR = 0.53; 95% CI:0.42–0.66, p < 0.01) were less likely to visit the ED for attempted suicide. Conclusion Prosperous communities had the highest rate of attempted suicides, with the risk of attempted suicide increasing as individuals move from the least prosperous to more prosperous areas.